Pengaruh Biaya Operasional dan Penjualan terhadap Laba Bersih pada PT Aneka Tambang (Persero) Tbk. Periode 2019—2023 - Budiari, Metha Agnes; Kurniawan, Reza; Susilawati, Endang (Owner : Riset dan Jurnal Akuntansi, 2024)
The success of a company can be measured by where the company generates profits. This research aims to determine the influence of operational costs and sales on net profit partially or simultaneously at PT Aneka Tambang (Persero) Tbk. over a period of five years, namely the period 2019-2023. The method used in the research is a quantitative method of descriptive and associative research type. The data in this research is secondary data from the financial reports of PT Aneka Tambang (Persero) Tbk. taken from the Indonesian Stock Exchange page. Based on this research, it shows that net profit is not partially affected by operational costs, but net profit is partially affected by sales. Meanwhile, net profit is affected simultaneously by operational costs and sales.